Culture Based Education: Efforts to Shift The Meaning of Self-Enrichment Ritual to The Spiritual Meaning of Grave Pilgrimage at Gunung Kemukus - Miftah, Muhammad; Musmuallim, Musmuallim (The Pontianak State Institute of Islamic Studies, 2021)
Gunung Kemukus is one of the religious tourist destinations that have the charm of Pangeran Samudera’s tomb located in Sragen Regency, Central Java. Pangeran Samudera is known as an Islamic disseminator of Majapahit descent who received religious guidance from Sunan Kalijaga. In its history, there has been a deflection of misleading traditions, this place is used as a cult of seeking wealth (pesugihan). It is said that to get a pesugihan, visitors must perform the seven times sexual adultery ritual on Jumat Pon. In fact, the culture of grave pilgrimage has become a tradition for the people of Sragen, Central Java, which has spiritual value for generations. Pilgrims send prayers to Pangeran Samudera and his grave experts as wasilah (bridge) to ask for his intention. The tradition that has taken root and believed by some people is used by individuals who are considered heretics for incidental-pragmatic interests through pesugihan rituals. This will bring a bad image to the noble culture that contains the value of local wisdom. Local culture that contains the values of simplicity, mutual cooperation and having spiritual-communal power has been littered with misleading traditions. If this misleading ritual practice is allowed, it will uproot the roots of the culture of a noble society. Because, cultural entities are noble, containing ethical values that teach human life behavior for a complete life. This research will discuss cultural-based educational efforts that attempt to shift the meaning of the misguided pragmatic rituals to the spiritual meaning of the pilgrimage to the grave in the glorious Pangeran Samudera tomb complex